O tango livre: considerações de um tangueiro (dançarino e professor) ao método de Rodolfo Dinzel. - Siqueira, Leonardo Pádua (2017)
In which way is the relation between the historical context, the imagination of the Argentine tango and the Dinzel teaching method able to contribute for the education and learning of the tango? This was the question that guided this dissertation project. This text presents historical socioculturally contextualized data; it summarizes the teacher and Tanguero Rodolfo Dinzel’s dance method and its practical applications. Interspersed with these contents, the author reveals his findings as a Tanguero and tango teacher throughout this study; and along with his findings, he makes contextual contributions considering his personal tango practice. The goal of this dissertation, which is focused on the area of artistic practices and processes of the Postgraduate Program in Arts of UFU, is to offer a functional text for the education and learning process of the tango, in an environment that can go beyond the university walls. Proposed as a tool to continuously reinvent the way of teaching tango, this dissertation aims to facilitate the creation of a meaningful experience of the learning process. In this perspective, students are invited to discover their own way of dancing. As a conclusion, one can say that the Dinzel method is able to contribute exponentially to the quality and awareness in the tango dance.